Essential oil from the roots of Paeonia lactiflora pall. has protective effect against corticosterone-induced depression in mice via modulation of PI3K/Akt signaling pathway - Sun, Jia-Yi; Liu, Yi-Tong; Jiang, Sheng-Nan; Guo, Peng-Mei; Wu, Xin-Yu; Yu, Jia (Frontiers in Pharmacology, 2022)
For thousands of years, the roots of Paeonia lactiflora Pall. (PLP) has been considered by traditional Chinese medicine as a drug that can improve mental or emotional disorders, including depression, anxiety and affective disorders. Unfortunately, the research on the mechanism of action and active ingredients of this beneficial drug is not comprehensive. This study focused on the activity of essential oil from PLP (EOP), systematically studied the antidepressant effect of EOP for the first time, and discussed the potential mechanism of its antidepressant effect. In this study, we used a mouse model of corticosterone (CORT)-induced depression, and found that EOP had a significant antidepressant effect on the symptoms of CORT-induced depression in mice, and significantly down-regulated the levels of CRH, ACTH and cortisol in the brain tissues of mice. In addition, we found that EOP treatment alleviated CORT-induced hippocampal neuron injury in mice In vitro experiments. It was also found that EOP could inhibit CORT-induced apoptosis and improve the proliferation ability and cell viability of PC12 cells. Further, with the help of network analysis, it was revealed that PI3K-Akt might be one of the main signaling pathways of EOP against CORT-induced hippocampal neuron apoptosis. In this study, we also found that EOP up-regulated the phosphorylation of PI3K and Akt in CORT-induced mouse hippocampal neurons and PC12 cells, and promoted the nuclear transcription of Nrf2 in CORT-induced PC12 cells. In conclusion, with the integrated approach, we demonstrated that EOP exerted anti-apoptotic effects on hippocampal neurons through PI3K/Akt/Nrf2 signaling pathway.